Silica Bound Sulphonic Acid Functionalized Imidazolium Ionic Liquid as a Recyclable and Recoverable Catalyst for N-Boc Protection of Amines - Kaur, Amanpreet; Singh, Vasundhara (Current Catalysis, 2014)
In the present work, silica supported imidazolium based sulphonic acid was developed via a simple route as a hybrid organic-inorganic solid acid catalyst. The covalent anchoring to the silica support gave a stable catalyst in quantitative yield, while the ionic tag assisted in increasing the solubility of the reactants to facilitate the reaction under solventless conditions, being a homogeneous -heterogeneous catalytic system and having the distinct advantages of both. The catalytic efficacy of the solid acid catalyst was tested for the N-Boc protection of amines. The reactivity order followed by amines was aliphatic >aromatic> hetrocyclic>aminoalcohols. This efficient protocol has advantages of better workability of catalyst, reduced reaction time, improved yield, high TON and the catalyst is both recyclable and recoverable upto seven cycles.
Keywords: organic-inorganic hybrid catalyst